STRATEGI KOMUNIKASI PEMASARAN MELALUI PERIKLANAN PUBLIC RELATIONS - Dewi Shanti Nugrahani (FE Program Studi Manajemen, 2006)
Marketing communication is needed by the company to communicate its product to cunsumer. One of the strategy for doing marketing communication is through public relations advertising. The form of PR advertising is corporate advertising which has aim to build the image and good will of company. The image and goodwill of company will support the activity of advertising company, so the consumer is eager to consumme the product of the company. Keywords: marketing communication, public relations, corporate advertising